PENGARUH KOMPETENSI DAN AKTIVITAS KOMITE AUDIT TERHADAP MANAJEMEN LABA - Kusumaningtyas, Metta (PRESTASI, 2013)
Abstract The objective of this study is to analyze the influence of the competence and activities of the audit committee on earnings management. Earnings management in this study were measured by using the value of discretionary accrual. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2008-2009. Based on purposive sampling method, the number of samples in this study of 65 samples. Testing the hypothesis using multiple regression analysis. The results of hypothesis testing indicate that audit committee competence, and audit committee activity had a significant negative effect on earnings management. Keywords : earnings management, audit committee, insitutional ownership.